Altered Nasal Microbiota-Metabolome Interactions in Allergic Rhinitis: Implications for Inflammatory Dysregulation - Ma Q; Wang N; Zheng X; Liu J; Che Y; Wang J (Journal of Inflammation Research, 2025)
Qianzi Ma,1,2 Nan Wang,3 Xingyue Zheng,1 Junjie Liu,1 Yanlu Che,4 Jingting Wang2 1Department of Otorhinolaryngology-Head and Neck Surgery, The Second Affiliated Hospital, Harbin Medical University, Harbin, People’s Republic of China; 2Department of Otorhinolaryngology of The Sixth Affiliated Hospital, School of Medicine, South China University of Technology, Foshan, People’s Republic of China; 3Department of Otolaryngology, Qingdao Women and Children’s Hospital, Qingdao, People’s Republic of China; 4Department of Otorhinolaryngology-Head and Neck Surgery, The Fourth Affiliated Hospital, Harbin Medical University, Harbin, People’s Republic of ChinaCorrespondence: Jingting Wang, Email 5433@hrbmu.edu.cnObjective: The aim of this study was to investigate the correlation between nasal microbiome, metabolites, and their potential contribution to the pathogenesis of allergic rhinitis (AR), a widespread chronic inflammatory disorder that poses a considerable healthcare burden worldwide. Immune dysregulation and environmental factors are key in the development of allergic responses, but the importance of host-microbiota interactions in influencing these responses is gaining recognition.Methods: 32 AR patients and 20 healthy controls underwent 16S rDNA sequencing and untargeted metabolomics analysis. Microbial diversity, composition, and functional pathways were compared between groups. Metabolomic alterations were evaluated using LC-MS/MS, and correlations between microbiota and metabolites were analyzed.Results: While α-diversity did not differ significantly between groups, β-diversity analysis revealed distinct microbial community shifts in AR patients. Specifically, Actinobacteria and Bacteroidetes abundances were increased, and genera Vibrio and Aeromonas were significantly enriched. Metabolomic profiling identified 528 differential metabolites, including altered levels of LPC, and pathway analysis highlighted disrupted linoleic acid metabolism, arachidonic acid metabolism, and tryptophan metabolism. Correlation analysis revealed significant associations between specific microbial taxa (eg, Aeromonas, Vibrio) and metabolites (eg, LPC, arachidonic acid), suggesting a potential link between microbiota-derived metabolic shifts and inflammatory responses in AR.Conclusion: The perturbation of nasal microbiota-metabolite interactions may play a role in the pathogenesis of AR, emphasizing the need for future investigations into potential pathophysiological mechanisms.Keywords: allergic rhinitis, nasal microbiota, metabolomics, inflammation